Characteristics of Bleeding Peptic Ulcers and the Outcome after Endoscopic Therapy at a Tertiary Care Centre of Pakistan: Bleeding Peptic Ulcers and Endoscopic Therapy - Javed, Farwah; Hassan, Ghias Ul; Khalil, Hafiz Habib Ur Rehman; Rasool, Shafqat; Dilshad, Akif; Nasir, Bilal (Pakistan Journal of Health Sciences, 2024)
Peptic ulcers are a global health concern. Bleeding episodes, a common complication require urgent intervention. Endoscopic therapy for managing bleeding peptic ulcers offering both diagnostic and therapeutic benefits. Objective: To analyze the characteristics of bleeding peptic ulcers and assess the outcomes following endoscopic therapy. Methods: A descriptive case series was conducted at Lahore General Hospital (LGH) between June 2021 and January 2022. Patients aged 18-80 with upper GI bleeding due to peptic ulcers or undergoing endoscopy with bleeding peptic ulcers were included. An 80mg bolus of omeprazole was given, followed by infusion at 8mg per hour and an urgent endoscopy was planned. Patients were observed for re-bleeding for 72 hours post-endoscopy. Results: Out of total 100 patients with upper GI bleeding, 70% of patients were male and 30% were female. The most common diagnosis was duodenal ulcers (75%), with the anterior wall being the most common site (86.67%). Dual therapy was administered in all patients, with hemostatic clips being applied in 68% of patients and electrocoagulation heat therapy being used in 32% of patients. Initial hemostasis was successful in 88% of patients treated endoscopically. But, 12% of patients experienced heavy bleeding during endotherapy and out of these, 8 patients required urgent laparotomy. Patients needed a second look endoscopy, 4 patients requiring angiographic embolization and 6 being managed with endotherapy. Conclusion: Dual therapy, hemostatic clips and electrocoagulation heat therapy are effective in achieving initial hemostasis in most cases